Design and Development of Intelligent Fire-fighting Robot Based on STM32. Issue 6 (January 2021) - Wu, Changzhong; Ge, Fan; Shang, Guangchao; Zhao, Mingpeng; Wang, Guitao; Guo, Hengshuai; Wu, Liang
Abstract: With the rapid growth of economy, fires occur frequently in various dangerous places. According to the investigation, in the ancient tragic fire cases, the number of intelligent mobile fire-fighting equipment is very small, and ordinary fire extinguishers and fire-fighting trains can't put out the fire in time and quickly. As a kind of robot, intelligent fire-fighting robot plays an increasingly important role in fire-fighting and rescue. In this paper, the design of fire robot is studied. Intelligent fire-fighting robot is mainly composed of fire-fighting movement system, fire-fighting water spray system, fire-fighting control system and other components. All parts cooperate with each other and work together to complete the fire-fighting task.